2003
DOI: 10.1046/j.1523-1755.2003.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

GW274150, a potent and highly selective inhibitor of iNOS, reduces experimental renal ischemia/reperfusion injury

Abstract: These results suggest that (1). an enhanced formation of NO by iNOS contributes to the pathophysiology of renal I/R injury and (2). GW274150 reduces I/R injury of the kidney. We propose that selective inhibitors of iNOS activity may be useful against renal dysfunction and injury associated with I/R of the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 54 publications
7
152
0
4
Order By: Relevance
“…The protective effects of NO seem to be associated with eNOS-derived NO, which causes vasodilation and inhibits leukocyte adhesion and platelet aggregation (31), whereas the damaging and proinflammatory effects have been associated with iNOS-derived NO, which forms the peroxynitrite anion from the interaction of NO and superoxide (32). The plasma levels of nitrite (used as an indicator of NO formation) measured at the end of the 6-h reperfusion period indicate I/R-induced elevated NO production as demonstrated previously (10). This elevated NO has been proposed to account, in part, for the proinflammatory processes that occurs within the kidney and contribute to acute renal failure (9) and due in part to the generation of peroxynitrite.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The protective effects of NO seem to be associated with eNOS-derived NO, which causes vasodilation and inhibits leukocyte adhesion and platelet aggregation (31), whereas the damaging and proinflammatory effects have been associated with iNOS-derived NO, which forms the peroxynitrite anion from the interaction of NO and superoxide (32). The plasma levels of nitrite (used as an indicator of NO formation) measured at the end of the 6-h reperfusion period indicate I/R-induced elevated NO production as demonstrated previously (10). This elevated NO has been proposed to account, in part, for the proinflammatory processes that occurs within the kidney and contribute to acute renal failure (9) and due in part to the generation of peroxynitrite.…”
Section: Discussionmentioning
confidence: 64%
“…Tyrosine nitration was detected in kidney sections by immunohistochemistry, as described previously (10).…”
Section: Immunohistochemical Localization Of Nitrotyrosinementioning
confidence: 99%
“…According to the report by Chatterjee et al (5), nitrite production in the primary culture of human proximal tubule cells was Ͻ5 nmol⅐mg protein Ϫ1 ⅐24 h Ϫ1 under the basal condition, whereas it exhibited a 10-fold increase after treatment with cytokines. They also demonstrated that the plasma level of nitrite/nitrate significantly increased in rats subjected to bilateral renal ischemia (6). Therefore, immune-inflammatory responses or some tissue damage might be involved in the NO-mediated modulation of K ϩ channel activity.…”
Section: Discussionmentioning
confidence: 95%
“…2). Although AST and LDH are not kidney-specific organ injury markers, they have been commonly used for indicating the severity of cellular injury in the kidney after IR (10)(11)(12). These findings correlated with the visible changes that renal IRI caused on histopathologic examination.…”
Section: Wnt Agonist Decreases Renal Tissue Injurymentioning
confidence: 92%